2010
DOI: 10.1016/j.drugalcdep.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The association between alcohol-related arrests and college football game days

Abstract: Binge drinking has been tied to specific occasions, such as certain holidays and sporting events. However, previous research has relied almost exclusively upon self-reports of university students to document these associations. In order to address this limitation, the present study examined patterns of alcohol-related offenses occurring within the context of holidays and collegiate football games. Public arrest records from a university town with a successful NCAA Division I football program were examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
2
14
1
Order By: Relevance
“…Recent studies have suggested that collegiate American football games, in particular, represent a significant risk for heavy episodic drinking and related criminal activity, especially at universities where football success is highly-valued (Glassman et al, 2007; Neal and Fromme, 2007; Nelson and Wechsler, 2003; Merlo et al, 2010). While many American football fans are not affiliated with the universities, most studies have focused only on student alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that collegiate American football games, in particular, represent a significant risk for heavy episodic drinking and related criminal activity, especially at universities where football success is highly-valued (Glassman et al, 2007; Neal and Fromme, 2007; Nelson and Wechsler, 2003; Merlo et al, 2010). While many American football fans are not affiliated with the universities, most studies have focused only on student alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Late-night alcohol drinking and violence commonly occur after football events. 1,5,22 This could affect the incidence of homicides the day after football; these days were indicated and included in the analyses. In addition, we accounted for an overall trend during 2005 to 2008 by including two fractional polynomials, and we accounted for seasonality by including a sine-cosine pair with annual periodicity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This research suggests that homicide, disorderly conduct, and violent crime increase on certain major holidays (Cohn & Rotton, 2003; Lester, 1979; Rotton & Cohn, 2004). One study in a college town suggested that crime on holidays traditionally associated with alcohol use (e.g., New Year’s, St. Patrick’s Day) did not differ from non-holiday, non-football Saturdays (Merlo, Hong, & Cottler, 2010). However, the majority of holidays in that study occurred during university breaks, when many students were away.…”
Section: Community Impact Of College Student Drinkingmentioning
confidence: 99%